Size - resolved composition and morphology of particulate matter during the southwest monsoon in Metro Manila, Philippines - Cruz, Melliza Templonuevo (Archīum Ateneo, 2019)
This paper presents novel results from size-resolved particulate matter (PM) mass, composition, and morphology measurements conducted during the 2018 southwest monsoon (SWM) season in Metro Manila, Philippines. Micro-orifice uniform deposit impactors (MOUDIs) were used to collect PM sample sets composed of size-resolved measurements at the following aerodynamic cut-point diameters (Dp): 18, 10, 5.6, 3.2, 1.8, 1.0, 0.56, 0.32, 0.18, 0.10, and 0.056 µm. Each sample set was analyzed for composition of the water-soluble fraction. Analysis for mass was carried out on two sample sets, whereas black carbon (BC) and morphology analysis were analyzed on a single sample set. The bulk of the PM mass was between 0.18 and 1.0 µm with a dominant mode between 0.32 and 0.56 µm. Similarly, most of the black carbon (BC) mass was found between 0.10 and 1.0 µm, peaking between 0.18 and 0.32 µm. These peaks are located in the Greenfield gap, or the size range between 0.10 and 1.0 µm, where wet scavenging by rain is relatively inefficient. In the range between 0.10 and 0.18 µm, BC constituted 78.1 % of the measured mass. Comparable contributions of BC (26.9 %) and the water-soluble fraction (33.4 %) to total PM were observed and most of the unresolved mass, which amounted to 39.6 % in total, was for diameters exceeding 0.32 µm. The water-soluble ions and elements exhibited an average combined concentration of 8.53 µg m−3, with SO42-, NH4+, NO3-, Na+, and Cl− as the major contributors. Positive matrix factorization (PMF) was applied to identify the possible aerosol sources and estimate their contribution to the water-soluble fraction of collected PM. The factor with the highest contribution was attributed to “aged aerosol” (48.0 %), while “sea salt” (22.5 %) and “combustion” emissions (18.7 %) had comparable contributions. “Vehicular/resuspended dust” (5.6 %) and “waste processing” emissions (5.1 %) were also identified. Microscopy analysis highlighted the ubiquity of nonspherical particles regardless of size, which is significant when considering calculations of parameters such as single scattering albedo, the asymmetry parameter, and the extinction efficiency. The significant influence from aged aerosol to Metro Manila during the SWM season indicates that local sources in this megacity do not fully govern this coastal area's aerosol properties. The fact that the majority of the regional aerosol mass burden is accounted for by BC and other insoluble components has important downstream effects on the aerosol hygroscopic properties, which depend on composition. The results are relevant for understanding the impacts of monsoonal features on size-resolved aerosol properties, notably aqueous processing and wet scavenging. Finally, the results of this work provide contextual data for future sampling campaigns in Southeast Asia such as the airborne component of the Cloud, Aerosol, and Monsoon Processes Philippines Experiment (CAMP2Ex) planned for the SWM season in 2019.